صكوك مخالفة لأحكام الشريعة الإسلامية: دراسة تحليلية Non Shariah-Compliant Sukuk: An Analytical Study - AL-Issa, Abdul Hanan (International Journal of Al-Turath In Islamic Wealth and Finance, 2021)
تهدف الدراسة إلى بيان عدد من المخالفات لأحكام الشريعة الإسلامية، تضمنتها غالبية نشرات إصدار الصكوك القائمة على الأصول، المبنية على عقود الأمانة، وهي التعهد بالشراء بالقيمة الإسمية أو بسعر متفق عليه من مدير الصكوك، التعهد بالشراء بالقيمة الإسمية أو بسعر متفق عليه أو ضمان العوائد من طرف ثالث، تعهد حملة الصكوك ببيع الأصول بالقيمة الأسمية للصك، إقراض مدير صكوك الاستثمار لحملة الصكوك، ملكية حملة الصكوك للأصول العينيَّة في الصكوك المبنية/القائمة على الأصول، الشركة ذات الغرض الخاص Special Purpose vehicle (SPV)، وتوصلت الدراسة لعدة نتائج أهمها: أن الطرف الثالث الذي طرحته قرارات المجمع أو المعايير الشرعية، غير موجود على أرض الواقع، كما أن التكافل الإسلامي كصورة من صور الحماية، ما هو إلا صورة من صور الضمان، حيث أن الملكية النفعية التي هندست عليها ملكية حملة الصكوك للأصول، لا تتوافق مع الملكية المتوافقة مع مبادئ الشريعة الإسلامية، لأنها تقيد حق حملة الصكوك بالتصرف بالأصول، وكي تكون الصكوك متوافقة مع مبادئ الشريعة الإسلامية، تراعى المسائل التالية: نقل ملكية الأصول لاسم المالك الحقيقي (حملة الصكوك)، مما يتيح لهم صلاحيات وسلطات المالك على ملكه، من حيث التصرف ومن حيث تحمل المصروفات وتبعات الهلاك، اعتماد الصكوك المدعومة بأصول (Asset backed)، بشرط نفاذ حملة الصكوك للأصول بقيمتها السوقية. Abstract The purpose of the study is to clarify a number of violations of Islamic Shariah principles identified in the majority of asset-based sukuk issuance prospectuses, which are based on trust contracts. It is an agreement to purchase a sukuk from the sukuk management at face value or at an agreed-upon price. This is sukuk holders’ promise to sell assets for the face value of the sukuk, as well as lending by Investment Sukuk Manager to sukuk holders and ownership of tangible assets in asset-based sukuk i.e. Special Purpose Company that is well known as namely; Special Purpose vehicle. The study resulted in a number of findings. The most important of these is that the third party proposed by the council’s resolutions or Shariah Standards does not exist in fact, just as Islamic Takaful as a kind of protection and is simply regarded a guarantee since the beneficial ownership on which the sukuk holders’ ownership is established, seems incompatible with Shariah-compliant ownership. Because it restricts the right of sukuk holders to dispose of assets ensuring that the sukuk are compliant with Islamic Shari’ah principles. The following considerations should be taken: transferring the ownership of the assets to the name of the real owner (the holders of the sukuk), which gives them the powers and authorities of the owner over his ownership/property, in terms of disposition as well as in terms of bearing the expenses and the consequences of loss, adopting of the sukuk which are based on asset backed principle, assuming that the sukuk holders dispose of the assets at their market value. Keywords: Sukuk, Shariah, Contemporary applications.